The Association Between Cyclooxygenase-2 –1195G/A (rs689466) Gene Polymorphism and the Clinicopathology of Lung Cancer in the Japanese Population: A Case-Controlled Study - Sun , Rong; Tanino , Ryosuke; Tong , Xuexia; Isomura , Minoru; Chen , Li-Jun; Hotta , Takamasa; Okimoto , Tamio; Hamaguchi , Megumi; Hamaguchi , Shunichi; Taooka , Yasuyuki; Isobe , Takeshi; Tsubata, Yukari (Frontiers in Genetics, 2022)
The single nucleotide polymorphisms (SNPs) of cyclooxygenase-2 (COX-2), a pro-inflammatory factor, alter the risk of developing multiple tumors, but these findings are not consistent for lung cancer. We previously reported that the homozygous COX-2 1195A genotype is associated with an increased risk for developing chronic obstructive pulmonary disease (COPD) in Japanese individuals. COPD is a significant risk factor for lung cancer due to genetic susceptibility to cigarette smoke. In this study, we investigated the association between COX-2 1195G/A polymorphisms and lung cancer susceptibility in the Japanese population. We evaluated the COX-2 polymorphisms using a polymerase chain reaction-restriction fragment length polymorphism assay for 330 newly diagnosed patients with lung cancer, including 221 patients with lung adenocarcinoma, 85 patients with lung squamous cell carcinoma, and 162 healthy controls. Our results show that no relationship exists between COX-2 1195G/A polymorphisms and overall lung cancer diagnosis relative to the controls. However, the frequency of patients homozygous for COX-2 1195A is higher in the squamous cell carcinoma group relative to the control group, whereas no difference is observed for patients with adenocarcinoma homozygous for COX-2 1195A relative to the control group. Kaplan-Meier analysis shows that the frequency of homozygous COX-2 1195A does not correlate with the overall survival of patients with squamous cell carcinoma of the lung. In conclusion, the COX-2 1195A genotype confers an increased risk for squamous cell carcinoma of the lung in Japanese individuals and could be used as a predictive factor for early detection of lung squamous cell carcinoma.